Analisis Pemahaman Konsep Perkalian Matriks Dalam Pembelajaran Matematika Kelas 11 - Jvana Wahyu Pratami; Nabila Nabila; Rina Sunaryani (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
The research was conducted to determine students' ability to solve problems with matrix material. This study used descriptive qualitative research and took 20 class XI students of SMK Bina Bangsa as research objects. The techniques used to collect research data are 3 instruments in the form of question descriptions and questionnaire forms. Data analysis in this study used data reduction, data presentation, and drawing conclusions. As a result of this study, students of class XI at SMK Bina Bangsa did not do well in mastering the matrix material and understanding the concepts. The reason students find it difficult to master matrix concepts is because students do not have the necessary material such as fraction operations and negative number operations. The lack of practice questions is also a factor in students' lack of understanding of the determinants of matrices.